Hasta Uyum Ölçeğinin Türkçe Geçerlilik ve Güvenilirliği. - Gözübüyük, Onur (Hacettepe University Faculty of Health Sciences Journal)
Objectives: The aim of this study was to test the validity and reliability of the Turkish version of the Patient Compliance Scale to determine patients' compliance with treatment. Materials and Methods: The sample of the study consisted of 389 patients who applied to the outpatient clinic of a university hospital and were collected by the convenience sampling method. The personal information form and patient compliance scale were used as measurement tools. Confirmatory factor analysis, convergent validity and discriminant validity analyses, item-total correlation, and item analysis were performed, and the Cronbach Alpha reliability coefficient was used for internal consistency. Results: According to the findings of the researcher, the necessary compliance conditions for language equivalence, content validity, and construct validity of the patient compliance scale were met. The factor loadings of the scale ranged between 0.61-0.90. Cronbach's alpha value was determined to be 0.879. Conclusion: The results support that the patient compliance scale is a valid and reliable measurement tool. The scale was evaluated as a scale that can be applied to patients at both outpatient and clinical levels.